2017
DOI: 10.5144/0256-4947.2017.56
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofNigella sativasupplementation over a one-year period on lipid levels, blood pressure and heart rate in type-2 diabetic patients receiving oral hypoglycemic agents: nonrandomized clinical trial

Abstract: BACKGROUNDDiabetic patients with hypertension and dyslipidemia are at a high risk of cardiovascular complications.OBJECTIVESTo determine the effect of Nigella sativa supplementation on the lipid profile, mean arterial pressure, and heart rate in persons with type 2 diabetes on oral hypoglycemic agents (OHA).DESIGNSingle-blind, nonrandomized.SETTINGDiabetes clinic of a university hospital in Saudi Arabia.PATIENTS AND METHODSType-2 diabetic patients were recruited by purposive sampling and assigned to treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…It seems that the normal lipid profile of both groups at the beginning of the study is responsible for these results. Previous studies in patients with hyperlipidemia have shown that 2 g/day N. sativa supplementation reduces blood lipids significantly (Badar et al, ; Farzaneh et al, ; Sabzghabaee et al, ). The effects of black seed on the lipid profile are due to presence of antioxidants such as thymoquinone, tocopherol, and phytosterol, which can prevent LDL‐C oxidation, inhibit intestinal absorption of cholesterol, reduce the production of hydroxyl–methyl–glutaryl coenzyme A reductase (HMGCR), and improve the expression of LDL receptor genes by reducing intracellular cholesterol (Al‐Naqeeb & Ismail, ; Brufau, Canela, & Rafecas, ; Mariod, Ibrahim, Ismail, & Ismail, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It seems that the normal lipid profile of both groups at the beginning of the study is responsible for these results. Previous studies in patients with hyperlipidemia have shown that 2 g/day N. sativa supplementation reduces blood lipids significantly (Badar et al, ; Farzaneh et al, ; Sabzghabaee et al, ). The effects of black seed on the lipid profile are due to presence of antioxidants such as thymoquinone, tocopherol, and phytosterol, which can prevent LDL‐C oxidation, inhibit intestinal absorption of cholesterol, reduce the production of hydroxyl–methyl–glutaryl coenzyme A reductase (HMGCR), and improve the expression of LDL receptor genes by reducing intracellular cholesterol (Al‐Naqeeb & Ismail, ; Brufau, Canela, & Rafecas, ; Mariod, Ibrahim, Ismail, & Ismail, ).…”
Section: Discussionmentioning
confidence: 97%
“…They were milled every 4 weeks, placed in the capsules, and delivered to the participants. We chose 2 g/day because previous studies have reported the beneficial effects of this dosage on other health-related outcomes (Badar et al, 2017;Farzaneh, Nia, Mehrtash, Mirmoeini, & Jalilvand, 2014;Hussain, Tunio, Arain, & Shaikh, 2017;Sabzghabaee, Dianatkhah, Sarrafzadegan, Asgary, & Ghannadi, 2012). N. sativa seeds contain protein (26.7%), fat (28.5%), carbohydrates (24.9%), crude fiber (8.4%), and total ash (4.8%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the literature search, four articles were found to be eligible for this evidence-based case report [13][14][15][16] the design and summary of the articles can be found in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…These two articles are prospective cohort studies with a level of evidence of 2b. The study by Badar A, et al [13] has a larger sample size and longer duration compared with the study by Rizka A, et al [14]. The former is a single-blind non-randomized clinical trial, whereas the latter is a double-blind randomized controlled trial.…”
Section: Resultsmentioning
confidence: 99%